Golgi Complex Dynamics and Its Implication in Prevalent Neurological Disorders - Mario O. Caracci; Luz M. Fuentealba; María-Paz Marzolo (Frontiers in Cell and Developmental Biology, 2019)
Coupling of protein synthesis with protein delivery to distinct subcellular domains is essential for maintaining cellular homeostasis, and defects thereof have consistently been shown to be associated with several diseases. This function is particularly challenging for neurons given their polarized nature and differential protein requirements in synaptic boutons, dendrites, axons, and soma. Long-range trafficking is greatly enhanced in neurons by discrete mini-organelles resembling the Golgi complex (GC) referred to as Golgi outposts (GOPs) which play an essential role in the development of dendritic arborization. In this context, the morphology of the GC is highly plastic, and the polarized distribution of this organelle is necessary for neuronal migration and polarized growth. Furthermore, synaptic components are readily trafficked and modified at GOP suggesting a function for this organelle in synaptic plasticity. However, little is known about GOPs properties and biogenesis and the role of GOP dysregulation in pathology. In this review, we discuss current literature supporting a role for GC dynamics in prevalent neurological disorders such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and epilepsy, and examine the association of these disorders with the wide-ranging effects of GC function on common cellular pathways regulating neuronal excitability, polarity, migration, and organellar stress. First, we discuss the role of Golgins and Golgi-associated proteins in the regulation of GC morphology and dynamics. Then, we consider abnormal GC arrangements observed in neurological disorders and associations with common neuronal defects therein. Finally, we consider the cell signaling pathways involved in the modulation of GC dynamics and argue for a master regulatory role for Reelin signaling, a well-known regulator of neuronal polarity and migration. Determining the cellular pathways involved in shaping the Golgi network will have a direct and profound impact on our current understanding of neurodevelopment and neuropathology and aid the development of novel therapeutic strategies for improved patient care and prognosis.